The impact of malaria disease on productivity of rural farmers in Osun state, Nigeria - Adebayo, Ogunniyi; Olagunju, Kehinde; S. A, Adewuyi (Studia Mundi – Economica, 2015)
In developing countries, the impact of malaria on human health, productivity and human development is well profound. It possesses serious challenge to the survival of several vulnerable poor, whose livelihood depends solely on agriculture. This study was carried out to examine the impact of malaria on the productivity of arable crop farmers and further estimate the cost implication of malaria (direct and Indirect) in rural Nigeria. Data were collected from a random sample of 91 crop farmers through the use of a well- structured questionnaire. The data were analyzed using descriptive statistics and multiple linear regression. The mean age of the crop farmers was 48 years with only 87.9% percent headed by males. The household heads are largely had primary education. Specifically malaria prevalence, household size, farming experience and cost of malaria treatment were significant factors that influenced crop productivity in the study area. It recommended that public enlightenment under the aegis of the “Roll Back Malaria Campaign” should be intensified and treated mosquito bed nets should be provided at subsidized rates to arable crop farmers. Farmers on their part should keep clean environment. Due regard should be given to environmental sanitation in the rural farming communities in the state.